A Formation Composition for Fixed-wing UAV Using Leader-Follower Strategy Based on Potential Field in Leader's Fault Situation - Eom, Jaehyeok; Park, Jongho; Lim, Jaesung (Journal of the Korean Society for Aeronautical and Space Sciences, 2024)
In this paper, a problem of Unmanned Aerial Vehicle (UAV) formation maintenance in the leader-follower strategy is handled when the leader's fault occurs. A potential field based leader-follower strategy that is applicable even in leader's fault situation is proposed The proposed algorithm hands over the information and the role of the previous leader to one of the followers when the leader's fault occurs. Unlike conventional potential field strategies which cannot head toward the target in leader's fault situations, an advanced potential field presents a new target point which is the estimated position of the previous leader so that the UAVs can fly back to the target after formation reconstruction. Numerical simulation shows that the proposed algorithm is applicable in leader's fault situation and its performance is analyzed using indices such as distances between UAVs and trajectory tracking error.
Keywords: Collision Avoidance; Leader's Fault; Leader-Follower; Potential Field; UAV Formation